INTELLEGENT AUTOMATION IT OPERATION INTEGRATION OFAIOPS AND VOICE CONTROL SYSTEMS (American Journal of Pedagogical and Educational Research, 2026)
The article examines modern directions of applying artificial intelligence (AI) in cybersecurity. Key technologies of machine learning, neural networks, and intelligent data analysis used for threat detection, attack prevention, and incident response automation are analyzed. Particular attention is given to the advantages, limitations, and future prospects of AI-based solutions in the field of information security.